0821 Successful Sleep Extension and Phase Advance in Adolescents in Response to a Pilot Sleep/circadian Manipulation. (12th April 2019) - Hasler, Brant; Buysse, Daniel; Ngari, Wambui; Franzen, Peter
Abstract: Introduction: Developmental changes in sleep and circadian rhythms conflict with early school start times during adolescence, leaving many teens with insufficient sleep and circadian misalignment. Short sleep and circadian misalignment increase risk for substance use problems, which may be mediated by changes in brain reward and impulse control systems. In this pilot study, we examined the effects of a two-week sleep/circadian manipulation in adolescents on sleep timing/duration, circadian phase, and measures of reward and impulse control. Methods: We studied 10 healthy 13-15 year-olds (6 females) categorized as having late/short sleep based on published norms. During baseline and manipulation phases, participants monitored sleep via diaries and actigraphy for 14 days, followed by a 2- and 1-night laboratory visit (pre/post-manipulation). During laboratory visits, circadian phase was assessed via dim light melatonin onset (DLMO). Both visits included self-report measures and computer-based tasks assessing reward function (Behavioral Inhibition/Behavioral Activation Scales; Balloon Analogue Risk Task) and impulsivity (UPPS-P Impulsive Behavior Scale; Two-Choice Impulsivity Paradigm). During the 14-day manipulation, participants were asked to wear blue-blocker glasses for 2 hours before bed, go to bed 1.5 hours earlier, maintain a consistent rise time, and wear Re-Timer light goggles for 30 minutes each morning. Pre-Post manipulation changes were tested via paired t-tests. Results: Following the 14-day manipulation, all sleep timing measures and DLMO significantly advanced (mean change 0.35-1.65 hours; p-values ranged from <0.001 to 0.040) and total sleep time increased by 0.95 and 0.57 hours for diary (p=0.015) and actigraphy (p=0.012), respectively. No significant change was observed in any sleep continuity measures. Among the four reward and impulsivity measures, only the Two-Choice Impulsivity Paradigm showed a significant change (p=0.046): participants selected fewer smaller-sooner choices post-manipulation, indicating improved impulse control. Conclusion: We found preliminary evidence that a sleep/circadian manipulation can extend sleep, advance circadian timing, and reduce behavioral impulsivity in adolescents. Replication in a larger, controlled sample would suggest pathways by which sleep timing, sleep duration, and circadian alignment ultimately impact substance use. Support (If Any): Grant from University of Pittsburgh Brain Institute (McClung)